2020
DOI: 10.22271/plants.2020.v8.i6b.1234
|View full text |Cite
|
Sign up to set email alerts
|

Soxhlet extractor coupled with Liquid-liquid extraction: Setting up a pilot library of refined crude extracts from indigenous medicinal plants of Lesotho

Abstract: Infections associated with multidrug resistant organisms result in increased morbidity and mortality in Lesotho and globally, thus, there is immediate need to discover new antibiotics against resistant bacteria through systematic examination of inexpensive local herbs. Here, we report for the first time, the welldefined and publicly available prototype library that consists of 20 different crude extracts derived from crude drug samples of medicinal plants of Lesotho used for treatment of infectious diseases. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…[16] The root powder of T. asperata has been used in Lesotho traditional medicine to alleviate shoulder pain and for internal and external wounds. [3] In our previous study, [1] we reported the establishment of a prototype library of crude extracts derived from samples of medicinal plants of Lesotho used for the treatment of infectious diseases as our effort to advance search for novel secondary metabolites with potential pharmaceutical applications. In spite of their wide usage in folk remedies, K. capensis and T. asperata are still underexplored.…”
Section: Kedrostis Capensis a Meeuse Belongs To The Familymentioning
confidence: 99%
See 3 more Smart Citations
“…[16] The root powder of T. asperata has been used in Lesotho traditional medicine to alleviate shoulder pain and for internal and external wounds. [3] In our previous study, [1] we reported the establishment of a prototype library of crude extracts derived from samples of medicinal plants of Lesotho used for the treatment of infectious diseases as our effort to advance search for novel secondary metabolites with potential pharmaceutical applications. In spite of their wide usage in folk remedies, K. capensis and T. asperata are still underexplored.…”
Section: Kedrostis Capensis a Meeuse Belongs To The Familymentioning
confidence: 99%
“…The extracts were prepared using Soxhlet extractor followed by liquid-liquid fractionation according to the procedure reported by us. [1] Each of the 44.29 g of K. capensis and 50.22 g of T. asperata samples was refluxed at 78°C using 500 mL of solvent systems; ethanol/water (9:1 v/v), in Soxhlet extraction apparatus Ace Glass Incorporated, Vineland, NJ.…”
Section: Extractionmentioning
confidence: 99%
See 2 more Smart Citations